"Going episodic": collaborative inhibition and facilitation when long-married couples remember together. Issue 8 (14th September 2017) - Harris, Celia B.; Barnier, Amanda J.; Sutton, John; Keil, Paul G.; Dixon, Roger A.
ABSTRACT: Two complementary approaches to the study of collaborative remembering have produced contrasting results. In the experimental "collaborative recall" approach within cognitive psychology, collaborative remembering typically results in "collaborative inhibition": laboratory groups recall fewer items than their estimated potential. In the cognitive ageing approach, collaborative remembering with a partner or spouse may provide cueing and support to benefit older adults' performance on everyday memory tasks. To combine the value of experimental and cognitive ageing approaches, we tested the effects of collaborative remembering in older, long-married couples who recalled a non-personal word list and a personal semantic list of shared trips. We scored amount recalled as well as the kinds of details remembered. We found evidence for collaborative inhibition across both tasks when scored strictly as number of list items recalled. However, we found collaborative facilitation of specific episodic details on the personal semantic list, details which were not strictly required for the completion of the task. In fact, there was a trade-off between recall of specific episodic details and number of trips recalled during collaboration. We discuss these results in terms of the functions of shared remembering and what constitutes memory success, particularly for intimate groups and for older adults.